Contribution to the taxonomy, identification, and biogeography of the Palaearctic species of Bathyplectes Förster and Leptoperilissus Schmiedeknecht (Hymenoptera: Ichneumonidae: Campopleginae) - Vas, Zoltán (Zootaxa, 2023)
Two new species are described, Bathyplectes dbari sp. nov. from Turkmenistan, and Leptoperilissus horstmanni sp. nov. from Algeria, along with discussion on the generic placements, and with notes on the identification of the species. Additionally, 23 new Palaearctic distributional records of 11 species are given: Bathyplectes anurus (Thomson) from Armenia, Russia; B. aspergus Dbar from Bosnia and Herzegovina, Greece, Syria; B. cingulatus (Brischke) from Hungary; B. clypearis (Horstmann) from Romania; B. curculionis (Thomson) from Algeria, Crete, Hungary, Sicily, Syria; B. exiguus (Gravenhorst) from Armenia; B. infernalis (Gravenhorst) from Algeria; B. nigridens (Horstmann) from Algeria; B. quinqueangularis (Ratzeburg) from Kosovo and Mongolia, the latter represents the first record of the species from the Eastern Palaearctic region; B. rostratus (Thomson) from Hungary, Spain; B. tibiator (Gravenhorst) from Hungary, Montenegro, North Macedonia, Turkey. Furthermore, some formerly published erroneous distributional records are corrected.